Adaptive Synchronization for Hyperchaotic Liu System - Li, Shunjie; Wu, Yawen; Zheng, Gang (Frontiers in Physics, 2022)
In this paper, the adaptive control design is investigated for the chaos synchronization of two identical hyperchaotic Liu systems. First, an adaptive control law with two inputs is proposed based on Lyapunov stability theory. Secondly, two other control schemes are obtained based on a further analysis of the proposed adaptive control law. Finally, numerical simulations are presented to validate the effectiveness and correctness of these results.